Factors related to the disaster preparedness of patients on haemodialysis from Sichuan, China, during COVID‐19: A cross‐sectional study - Linfang Zhu; Yang Liu; Sijian Li; Ruoxi Liao; Ping Fu; Huaihong Yuan (Wiley, 2024)
Abstract Aim This study aimed to investigate personal preparedness among patients on haemodialysis (HD) and to examine the relationship among sociodemographic characteristics, attitudes toward disaster preparedness and personal preparedness behaviours during natural disaster incidents. Design A cross‐sectional survey was conducted. Methods A convenience sampling method was used. A total of 446 participants from six areas of Sichuan province completed the online questionnaire study from February 27 to March 13, 2022. Sociodemographic characteristics, attitudes toward disaster preparedness and personal preparedness behaviours were measured. Descriptive statistics were used to analyse sociodemographic characteristics and attitudes toward disaster preparedness. The relationship among sociodemographic characteristics, attitudes toward disaster preparedness and personal preparedness behaviours were assessed using ordinal regression. Statistical significance was defined as p < 0.05. Results A total of 446 participants completed the survey. Of these, 42.15% (N = 188) were poorly prepared, 26.23% (N = 117) were moderately prepared and 31.61% (N = 141) were highly prepared. Ordinal regression showed that knowing about disaster preparedness (Odds Ratio (OR) = 1.691, 95% Confidence Interval (CI) = 1.081-2.644, p = 0.021), participating in disaster evacuation exercises (OR = 2.519, 95% CI = 1.595-3.977, p < 0.001) and learning about disaster preparedness (OR = 2.421, 95% CI = 1.542-3.802, p < 0.001) were associated with high preparedness. Compared to patients with a university degree or higher, patients with a junior high school education or lower (OR = 3.491, 95% CI = 1.760-6.925, p < 0.001) and senior high school degree (OR = 2.052, 95% CI = 1.038-4.057, p = 0.039) were associated with high preparedness. Patients who felt very confident and could deal with all their needs (OR = 3.878, 95% CI = 2.904-7.181, p < 0.001) or patients who felt confident and could meet some of their needs (OR = 1.949, 95% CI = 1.124-3.379, p = 0.017) had higher preparedness than those who felt less confident and were not well prepared to take care of their needs. Patient or Public Contribution After obtaining each participant's consent, they filled out the online questionnaire using their own or a relative's cell phone while undergoing HD. Implication for Practice It is essential that patients should be educated not only on medical specialty topics, but also on general disaster preparedness. Medical institutions should improve and reinforce preparation training among targeted populations. The low level of preparedness is partly due to the lack of participation of patients in disaster preparedness programs. Dialysis center managers should be urged to implement such programs at their centers.